Distribution and association of visual impairment with myopic maculopathy across age groups among highly myopic eyes – based on the new classification system (ATN). Issue 4 (4th October 2021) - Ye, Luyao; Chen, Qiuying; Hu, Guangyi; Xie, Jiamin; Lv, Hanyi; Shi, Ya; Yin, Yao; Zhu, Jianfeng; Fan, Ying; He, Jiangnan; Xu, Xun
Abstract: Purpose: To investigate the percentages and risk factors for visual impairment (VI) across age groups in a highly myopic cohort with a wide range of age (18–93 years). Methods: A total of 2099 eyes (1220 participants) were enrolled. All participants underwent detailed ocular examinations. Myopic maculopathy (MM) was assessed as myopic atrophy maculopathy (MAM), myopic traction maculopathy (MTM) or myopic neovascular maculopathy (MNM) based on the ATN system. Results: Most participants younger than 50 years had normal vision, while the cumulative risk of VI and blindness gradually increased after 50–59 years. The percentage of each type of MM increased nonlinearly with ageing (all p < 0.001), with an accelerated period of increase after 45 years for MAM, and after 50 years for MTM and MNM. Axial length (AL) ≥30 mm was the only associated factor for mild VI or worse in participants aged 18–39 years (p < 0.001). Older age, AL ≥30 mm and the presence of MAM were predictors for mild VI or worse in the group aged 40–49 years (all p < 0.05). In participants aged ≥50 years, older age, female sex, longer AL and increased severity of MM were risk factors for VI and blindness (all p < 0.05). Conclusion: The percentages of MM and related VI increased nonlinearly with older age, with a turning point at 45 years for MAM, preceding that of MTM, MNM and VI by 5 years, warranting future longitudinal studies to confirm. Different age groups presented different risk factors for VI. Timely screening should be in place for middle‐aged high myopes.